Pelatihan MS Excel Untuk Meningkatkan Ketrampilan Staf dan Guru dalam Mengelola Data pada SMA Mahapatih Mojopahit Ciledug Tangerang - Tatang Wirawan Wisnuadji; Arsanto Narendro (AMMA : Jurnal Pengabdian Masyarakat, 2022)
If we look at the ability to carry out routine administrative work, we see that there are several factors that need to be improved, so that the performance of the teaching staff at SMA Mahapatih Mojopahit Tangerang can be improved for the better. As it is known that office administrative work to support the teaching and learning process is very important. Because the management of school student data and the administrative process will lead to the success of teaching and learning in schools. So our goal as partners feels the need to increase cooperation in the form of skills training in the use of software packages, especially software that is commonly used in schools to manage student data and other administrative data. We chose MS Excel as the main material in the training because this software package is easy and practical to use for training school staff. Starting with teaching how to operate the software properly and correctly, and followed by examples and applications in making tables and simple calculations. The result of this training is an increase in the skills of school administration and teaching staff, so that performance in the administrative field which is an important factor in the teaching and learning process can be achieved more effectively and efficiently.